Good Corporate Governance Sebagai Pemoderasi Pengaruh Profitabilitas dan Corporate Social Responsibility pada Nilai Perusahaan - Indra Wijaya, I Putu; Putu Wirawati, Ni Gusti (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p22, 2019)
The purpose of this study is to obtain empirical evidence regarding GCG as a moderating effect of profitability and CSR on the value of the companies of all companies listed on the Stock Exchange for the period 2013-2016. The results of the study found that profitability and CSR had a positive effect on firm value. GCG is able to strengthen the influence of CSR on corporate value, but GCG is not able to moderate the effect of profitability on company value. The results of this study are expected to be able to provide information for companies regarding the importance of increasing profitability, CSR disclosure and GCG implementation so that later it can increase the value of the company. The results of this study are expected to be able to provide information for interested parties as a basis for making investment decisions. Keywords : Firm value, profitability, CSR, GCG